191k views
0 votes
In the diagram, m_1= (6x + 12) and m_2 = (9x – 4)º.

In the diagram, m_1= (6x + 12) and m_2 = (9x – 4)º.-example-1
User Pot
by
4.6k points

1 Answer

4 votes

1 and 2 are vertically opposite angles and hence they must be equal.


\sf \: m \angle1 \: = m\angle2 \\ \sf \longrightarrow 6x + 12 = 9x - 4 \\\sf \longrightarrow9x - 6x = 12 + 4 \\\sf \longrightarrow3x = 16 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\\sf \longrightarrow \: x = (16)/(3) \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\\sf \longrightarrow \: x = 5. \overline{3} \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\\sf \leadsto \: \underline{ \boxed{ \sf{ \color{deeppink} \: {x \approx \: 5.3 \: }}}}\: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \:

User Mike Manard
by
4.5k points